2013
DOI: 10.1158/0008-5472.can-12-2221
|View full text |Cite
|
Sign up to set email alerts
|

Specific Elimination of CD133+ Tumor Cells with Targeted Oncolytic Measles Virus

Abstract: Tumor-initiating cells (TIC) are critical yet evasive targets for the development of more effective antitumoral strategies. The cell surface marker CD133 is frequently used to identify TICs of various tumor entities, including hepatocellular cancer and glioblastoma. Here, we describe oncolytic measles viruses (MV) retargeted to CD133. The viruses, termed MV-141.7 and MV-AC133, infected and selectively lysed CD133 þ tumor cells. Both viruses exerted strong antitumoral effects on human hepatocellular carcinoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 50 publications
0
86
0
4
Order By: Relevance
“…Several groups have described the generation of CSC-specific CD8 C T cells in vitro; 10,11 the killing of CSCs via non-specific immune cells 12,13 as well as by oncolytic viruses 14 and antibodies. 15 We have reported that CXCR1 blockade selectively targeted human breast CSCs in vitro and in xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have described the generation of CSC-specific CD8 C T cells in vitro; 10,11 the killing of CSCs via non-specific immune cells 12,13 as well as by oncolytic viruses 14 and antibodies. 15 We have reported that CXCR1 blockade selectively targeted human breast CSCs in vitro and in xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…Other engineered pan-cancer-specific OVs have also shown efficacy in preclinical HCC models, including OVs whose genome expression is driven by survivin, an inhibitor of the apoptosis protein family that is overexpressed in the majority of HCC cases (survivin promoter-regulated oncolytic adenovirus vector carrying TP53 gene, AdSurp-P53), and human telomerase reverse transcriptase (hTERT), expressed in up to 90 % of HCCs, but only some 20 % of non-malignant liver cells (hTERT promoter-regulated replicative adenovirus, SG300) (Kannangai et al, 2005; He et al, 2012; Nagao et al, 1999; Liu et al, 2011). More recently, OVs that preferentially target tumour-initiating cells have been engineered, including oncolytic measles virus retargeted to CD133-positive cells (Bach et al, 2013). In the liver, CD133 expression is limited to cancerous tissue, and is associated with colony formation and high proliferative capacity (Kohga et al, 2010;Zhu et al, 2010).…”
Section: Targeting Malignant Hepatocytesmentioning
confidence: 99%
“…Oncotarget 6 (11), 8788-8806 (2015). Molecular targeting of malignant glioma (GBM), an aggressive terminal brain tumor, is mediated through recognition of cellular receptors presented on the cells surface [7]. Taking into account broad variability of glioma cellular surface markers, exploring the differential expression of proteins on the surface of cancer cells is the key to targeting glioma and therapeutic payloads.…”
Section: -Written By Joonseok Leementioning
confidence: 99%